The Psychometric Properties of the Norwegian version of Mood and Feelings Questionnaire (MFQ) - Richter, Jörg; Sund, Anne Mari (PsykTestBarn, 2013)
Description: The Mood and Feelings Questionnaire (MFQ) is a self-report form assessing depressive symptoms related to the DSM-III-R (DSM-IV) in children and adolescents (aged 8 – 18). The questionnaire consists of 34 items with three response alternatives. The adolescents are asked how they have been feeling over the last two weeks. A test score is calculated as the sum of the item scores. Psychologists, physicians, other health care personnel with a master’s degree, teachers with a master’s degree and specialist teachers, who all have received psychological test administration training, are qualified to administer the MFQ. Literature search: Our systematic literature search for documentation of psychometric properties of the MFQ identified 30 references from Norwegian studies; three articles derived from the project Norwegian Universal Preventive Program for Social Anxiety (NUPP-SA); 20 articles were based on data from the study “Youth and mental health” at the Norwegian University of Science and Technology, Trondheim; and seven reported on the short version of the MFQ. Psychometrics: Test related norms were not published in any of the articles included in this systemetic review, but they can be requested from the translator of the Norwegian MFQ version, Anne Mari Sund (NTNU). Internal consistency and test-retest reliability were reported to be very good. Convergent validity was reported to be good, indicated by high correlation coefficients of MFQ scores with scores of the Beck Depression Inventory (BDI), relevant scales of the YSR in terms of the anxiety-depression syndrome scale, internalizing problems scale and with the aggressive symptom scale. Good discriminant validity was shown by a low correlation coefficient with social desirability. Conclusion: There is evidence for the MFQ’s psychometric properties, such as construct validity, convergent validity and reliability. However, this is exclusively related to the 13 – 15 age group and a particular area of Norway. Therefore, application of the MFQ can be recommended for Norwegian adolescents (aged 13-15), both in epidemiological and in clinical samples.